A MODEL OF TRANSFORMATION OF A CHILD'S TRAUMATIC EXPERIENCES HIBUKI THERAPY METHOD (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2024)
Background. The article is devoted to the description of the model of transformation of a child's traumatic experiences, which is part of the concept of Hibuki therapy, which is being actively implemented in Ukraine now by Israeli and Ukrainian psychologists.Methods. Modeling of a constructed ideal object-based on the identification of relationships between variables for the purpose of further verification for solving applied problems in the field of psychotherapy for children's trauma.Results. The presented model is a methodologically justified system that reflects the structural and functional connections of the recovery of the psyche of children of primary school age under the influence of therapeutic interventions with the help of a doll – a dog (Hibuki). It is assumed that children project their feelings and anxieties onto the toy object, identifying with these feelings and regulating emotions while caring for the Hibuki. The model reflects four levels of a child's mental functioning, which are the main "targets" of interventions in Hibuki therapy: emotional, cognitive, behavioral, physical. The spheres of traumatic experiences of younger schoolchildren are described, which meet certain criteria and expected results. Cognitive – reflective sphere. Criterion: awareness and understanding. Expected result: overcoming traumatic memories of past events. Emotional – affective sphere. Criterion: empathy and optimism. Expected result: stabilization of psycho-emotional state. Motivational and behavioral sphere. Criterion: attitude and effectiveness. Expected result: the ability to receive and provide support, establishing contacts and interactions. Physical and somatic sphere. Criterion: restoration of the body's functional capabilities. Expected result: recovery of physical activity.Conclusions. It is assumed that the complexity of the psychotherapeutic influence on various spheres of the child's psyche starts the process of personality dissociation, leads to the transformation of traumatic experiences, which are gradually integrated into the general picture of life.
Keywords: child trauma; Hibuki doll; Hibuki therapy method; model of transformation of child's traumatic experiences; trauma psychotherapy